-1x+(3-x)=2x-7

Simple and best practice solution for -1x+(3-x)=2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1x+(3-x)=2x-7 equation:



-1x+(3-x)=2x-7
We move all terms to the left:
-1x+(3-x)-(2x-7)=0
We add all the numbers together, and all the variables
-1x+(-1x+3)-(2x-7)=0
We get rid of parentheses
-1x-1x-2x+3+7=0
We add all the numbers together, and all the variables
-4x+10=0
We move all terms containing x to the left, all other terms to the right
-4x=-10
x=-10/-4
x=2+1/2

See similar equations:

| 2/3x+1/4x=2 | | 5m/8-6/8+3m/8=@/8 | | 3/4=x-3/8 | | 4.5(x-9)=2.96 | | 7x=x-870 | | 6x-37+8x-99=180 | | -9.04-3(0.2q-1)=-18.28 | | 3+2x+-1x+-1=3x+-6 | | 1.5^x=3.72 | | –1.6p=8 | | 4x+3.4=9.1 | | 1/4x+5/12x=4 | | 5x+24=2x-9-3x | | 3/4x+5=1/2x+15 | | 0.08(y-3)+0.16y=0.04y-0.5 | | 7×3x=23 | | –1.6x=8 | | 6x+11=10x-25 | | 3h+1=5.50 | | -3w^2+10w+8=0 | | 3h-1=5.50 | | x+6(x-1)=7(+x) | | 2/7x-2=9/7x | | -1+b/3=5 | | 1/4w-4/3=-4/5 | | 6x-8-2x=-18 | | 4n/9+1/3n=14/6 | | 1.25e.75(8+e)=2−1.25e | | 40=1.6(d)-3.2 | | -10+v/2=-17 | | -30=t-32 | | 6x+5×2=46 |

Equations solver categories